Satisfacción del cuidado de enfermería al paciente adulto mayor en el Hospital Belén de Trujillo, 2019 - Diaz Graos, Nancy Anabela (2020)
The present investigation quantitative, descriptive cross-sectional. It was made with the purpose of determining the satisfaction of nursing care for the elderly patient of the medicine A and B services of the Hospital Belén de Trujillo,2019. The sample consisted of 50 elderly hospitalized patients, using the CARE Q questionnaire as a instrument. Conclusions 54% of elderly patients have a high satisfaction level of nursing care, 44% average, and 2% low. In the accessibility category, 72% have a high satisfaction level of nursing care, 26% average and 2% low; In the explains and facilitates category, 78% have a medium satisfaction level of nursing care, 14% low and 8% high; In the comfort category, 52% have a high satisfaction level of nursing care, 46% average and 2% low; In the anticipates category, 52% have a high satisfaction level of nursing care, 46% average and 2% low. In the maintains a relationship of trust category, 50% have a hgh satisfaction level of nursing care, 50% average, and 0% low and in the monitors and follow-up category, 58% have a high satisfaction level of nursing care, 42% average and 0% low.